Microwave Non-Destructive Testing Technique for Material Characterization of Concrete Structures via Electromagnetic Waves with FDTD - Sener, Ummu Sahin; Eker, Sebahattin (IEEE, 2020)
Concrete is a nonhomogeneous medium that contains coarse aggregate, sand (fine aggregate), cement powder, water and porosity. Microwave non-destructive testing (NDT) technique is used to simulate three layered media that contains air gap, coarse aggregate and a two layered media that contain rebar and void is modeled as closest to the reality. Interaction of electromagnetic wave and the concrete pile is utilized for numerical simulation. A Finite-Difference Time-Domain (FDTD) method with Perfectly Matched Layer (PML) Absorbing Boundary Condition (ABC) is proposed to simulate electromagnetic wave propagation in FRP tube and composite pile. 2D simulation of a wave generated from a point source at microwave frequencies is obtained by using MATLAB (R).
Keywords: cement-based samples; layered media; rebar; finite-difference time-domain simulation; perfectly matched layer; Engineering; Physics; Telecommunications